HEMATITE-CARBONATE ROCKS OF THE YUBILEYNOE MASSIVE SULFIDE DEPOSIT (SOUTH URALS): EVIDENCE OF REPLACEMENT OF SULFIDE CLASTS AND HYALOCLASTS - A.S. Tseluyko; N.R. Ayupova; D.A. Artemyev; M.A. Rassomakhin; V.A. Kotlyarov (Минералогия)
The article considers textural and structural features of hematite-carbonate rocks associated with carbonate-sulfide clastic ores of the Yubileynoe massive sulfide deposit, South Urals. Some hematitecarbonate rocks exhibit signatures of the replacement of sulfide clasts and hyaloclasts by hematite-carbonate material, classified as carbonate analogs of gossanites. The hematite-carbonate aggregates after sulfide clasts are characterized by inherited reniform-colloform, radial and crystalline-granular structures, as well as the inclusions of relict sulfides and tellurides. The hematite-carbonate aggregates after sulfide clasts contain the elevated concentrations of chalcophile (Cu, Zn, Pb, As, Sb, Bi, Te) and lithophile (Ti, Zr, V, W) trace elements. The hematite-carbonate clasts after hyaloclasts contain aggregates with globular structure and syneresis cracks and contain relics of chlorite. The matrix of hematite-carbonate rocks consists of calcite with inclusions and aggregates of dolomite, chlorite, quartz and apatite. Late sulfide mineralization (pyrite metacrystals, aggregates and veins of chalcopyrite and sphalerite) is characteristic of both hematite-carbonate rocks after sulfide clasts and hyaloclasts.